The diagnostic value of diffusion-weighted magnetic resonance imaging in characterization of musculoskeletal soft tissue tumors - Marwa Romeih (The Egyptian Journal of Radiology and Nuclear Medicine, 2018)
Purpose: To assess the utility of diffusion-weighted (DW) images and magnetic resonance imaging (MRI) in the detection and characterization of musculoskeletal soft tissue tumours (STTs) and in the determination of whether these tumours are benign or malignant. Patients and methods: A prospective study was performed between March 2016 and March 2017 that included all patients referred to the radio-diagnosis department for evaluation of musculoskeletal STTs. Contrast-enhanced MRI and DW images were performed for all included patients, and diagnoses were confirmed by biopsy and histopathological examination. Results: The apparent diffusion coefficient (ADC) of benign STTs was significantly higher than that of malignant (mean ± SD, −1.43 ± 0.56 × 10−3 mm2/s versus 0.74 ± 0.18 × 10−3 mm2/s, respectively (P < 0.001), ADC cut off value ≤1.10 × 10−3 mm2/s with a sensitivity of 83.3%, specificity of 72.7%, and PPV and NPP of 80%; the area under the receiver operating characteristic curve was = 0.892 (SE = 0.084, 95% CI (P < 0.001) and the Youden's index was calculated 58.4. Conclusion: To date, MRI has been considered the method of choice for the characterization of musculoskeletal STTs; however, DW-MRI with ADC mapping is a rapidly, valuable, non-invasive, non-contrast tool for reliably differentiating between benign and malignant STTs.